2014
DOI: 10.1371/journal.pone.0105623
|View full text |Cite
|
Sign up to set email alerts
|

Famous Landmark Identification in Amnestic Mild Cognitive Impairment and Alzheimer's Disease

Abstract: BackgroundIdentification of famous landmarks (FLI), famous faces (FFI) and recognition of facial emotions (FER) is affected early in the course of Alzheimer's disease (AD). FFI, FER and FLI may represent domain specific tasks relying on activation of distinct regions of the medial temporal lobe, which are affected successively during the course of AD. However, the data on FFI and FER in MCI are controversial and FLI domain remains almost unexplored.ObjectivesTo determine whether and how are these three specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
1
20
1
Order By: Relevance
“…Hart, 1988; Hodges et al, 1992; Ahmed et al, 2008; Joubert et al, 2010), buildings (e.g. Ahmed et al, 2008; Sheardova et al, 2014), living/non-living things (e.g. Silveri et al, 1991; Grossman et al, 1998) and events (e.g.…”
Section: Semantic Task-based Fmri Experimentsmentioning
confidence: 99%
“…Hart, 1988; Hodges et al, 1992; Ahmed et al, 2008; Joubert et al, 2010), buildings (e.g. Ahmed et al, 2008; Sheardova et al, 2014), living/non-living things (e.g. Silveri et al, 1991; Grossman et al, 1998) and events (e.g.…”
Section: Semantic Task-based Fmri Experimentsmentioning
confidence: 99%
“…We have shown that our ‘in-house’ developed the Famous Landmarks Identification Test, created with the help from our participants, could be useful in recognising early stages of AD 20. We have also tested the specificity of several standard memory tests for estimating hippocampal atrophy in the CBAS participants, which could have immediate implications for clinical practice 34…”
Section: Findings To Datementioning
confidence: 96%
“…The adaptation of the Mild Behaviour Impairment Checklist was graphically reworked after being consulted, with our participants increasing the rate of successful completion considerably. In the tests developed by our team, such as the Famous Landmark Identification Test20 or the Subjective Spatial Memory Complaints Questionnaire,21 we consulted our participants during the entire development process, including the selection of relevant items. Some of the items were generated from qualitative research, which always preceded the development of new questionnaires.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Being a core symptom of depression, cognitive dysfunction may be the underlying phenotype of affective disorders ( Miskowiak et al, 2016 ). The degree of cognitive impairment and the severity of disease were found to be associated with deficits in facial expression recognition ( Wiechetek Ostos et al, 2011 ; Sheardova et al, 2014 ). The deficits in facial expression recognition are related to cognitive functions such as working memory, attention, and even language ability ( Barrett et al, 2011 ; Heck et al, 2017 ; Leib, 2019 ).…”
Section: Introductionmentioning
confidence: 99%